Transversal Filter MMIC design for Multi-Gbit/s Optical CDMA Systems Diseño de Filtro Transversal Monolítico Integrado de Microondas ( MMIC) para los Sistemas Ópticos CDMA en el Régimen de Multi-Gbits/s - Jorge Aguilar Torrentera (Computación y Sistemas, 2005)
In this work, the approach of the distributed transversal filter for Optical CDMA systems is addressed. It demonstrates that pulse generation and correlation functions can be accomplished in the electrical domain for multi-Gbit/s systems. The practicalities of the approach were assessed using a state of the art GaAs MMIC process. A innovate transversal filter, which is termed the dual drain-line transversal filter, was proposed and designed for speed operations exceeding 40 Gbit/s. A new tap gain weight control technique was designed for the proposed topology so that the filter can be modelled with constant distributed characteristics. A framework based on mixed-mode scattering parameters was derived to investigate the various frequency responses of the filter. Similarly, time domain results based on the full parameters of the MMIC design proves the efficacy of the approach. The filter satisfies the first Nyquist criterion and is suitable for multi-Gbit/s CDMA systems.